Acute Cerebellitis and Myeloradiculitis Associated With SARS-CoV-2 Infection in Common Variable Immunodeficiency—A Case Report. (April 2022) - Lemus, Hernan Nicolas; Alkayyali, Miryam; Kim, Eonjung; Cunnigham-Rundles, Charlotte; Pyburn, Dewitt; Abrams, Rory
The role of the adaptive immune system in mediating COVID-19 is largely unknown. Therefore, it is difficult to predict the clinical course in patients with common variable immunodeficiency (CVID), a disease characterized by dysfunctional lymphocytes and impaired antibody production. We report a case of SARS-CoV-2 infection presenting as isolated neurological symptoms in a patient with CVID. The patient subsequently improved following steroids, intravenous immunoglobulin, and convalescent plasma (CP). The latter has been shown to be safe and efficacious in treating COVID-19 in patients with primary immunodeficiency. Recent data suggest that the mechanism of CNS injury in COVID-19 may be due to immunological dysregulation rather than direct viral-mediated injury. This case exemplifies the complex interaction between the brain, the immune system, and the SARS-CoV-2 virus.